Some social values driven from verses about believer's characteristics, and the educational applications of these values - Al-Qathami, Rawan Mansour Bakhit (Journal of Educational and Psychological Sciences, 2020)
This research aims at investigating some social values at Surat Almu'mnoon at the Holy Qura'n, as well as the effects of these values and their educational applications.The descriptive and the deductive methods are used in this research, The research deals with the definition of the believers, the social values, and some verses of the characteristics of believers and the social values included in them, in addition to the effects of these values and their educational applications.The most important findings of the research are: the promotion of virtue and prevention of vice include an inclusive meaning, which is the call for all what Allah loves and approves from the imposed right deeds which are acquaintance with people. Moreover, prevention of vice, taboos and things that contradict the right common sense.The values of for the promotion of virtue and prevention of vice are basics of the fundamentals of religion and are bulwarks for the believers that keep the people away from the temptations and the evil of sins and vice.
Keywords: educational values; believers; the Holy Qur’an